Análisis financiero a la empresa “Mercamax” de la ciudad de Loja, periodo 2020-2021. - Sarango Sarango, Rosa Maricela (2023)
The Curricular Integration Work entitled Financial Analysis of the Company "Mercamax" of the city of Loja, period 2020-2021, was developed with the objective of knowing the economic- financial situation of the company "MERCAMAX" during the periods 2020-2021. To comply with the general and specific objectives, we proceeded the application of the horizontal and vertical analysis to the statements of financial position and income statements of the company "MERCAMAX" where it was determined that in 2020 the company presents 98.61% and in 2021 98.44% of current assets, where merchandise is the main asset that the company has. In the year 2020, 67.45% and in the year 2021, 48.74% of current liabilities were determined, where it is evident that most of its debts are with third parties, with suppliers having the largest share, a situation that occurs because the owner acquires merchandise for short-term payment; equity in the year 2020 presents 32.55% and in the year 2021 is 51.26%, a situation that occurs due to an increase in profits from one year to another and the capital contributed by the owner, for the operation of the company. The income in the year 2020 and 2021 is represented by sales being the only account of this group, since it is a commercial company and is dedicated to the purchase and sale of staple products, the cost of sales in the year 2020 is 91.02% and in the year 2021 is 86, 53% generating a gross profit in the year 2020 of 8.98% and in the year 2021 of 13.47%, within the expenses the most significant subgroup are the administrative expenses in the year 2020 with 9.40% and in the year 2021 of 10.36% which are necessary in every company The horizontal analysis allowed to know which have been the variations that the accounts have suffered during these two years in the statements of financial position and income, where it showed that within the assets the group that presented more variation is the current assets, it includes the merchandise and what is owed to the company, within the liabilities and equity, the group of greater variation was current liabilities and equity, they are what the company owes to third parties and what the owner has contributed for the operation of the company. Regarding the statement of income, it was evidenced that the accounts with the highest variation were presented within the group of administrative expenses, which, being very high, influence the company's profit. To comply with the second objective, the financial indicators were applied in which are: liquidity, activity, indebtedness and profitability, where it was evidenced that in accounts payable the company exceeds the standard, forcing the owner to take new strategies to cover 5 on time with their payments, also in terms of inventory turnover the owner should know a little more about the products that have higher turnover because it has no variation of products and should be according to customer needs. And as a last part, the report of financial analysis was formulated through which is reflected in a general way about the practice of financial analysis applied to the company MERCAMAX, which will serve the owner for making timely decisions.